Non-healing pharyngeal ulcer in a middle-aged Caucasian man - Nwankwo, Nwabundo (BMJ Publishing Group, 2013)
Extranodal natural killer NK/T-cell lymphoma is a rare malignancy. The disease is common in some Asian countries such as China, Japan as well as in South America. We present a case of extranodal NK/T-cell lymphoma which presented as a pharyngeal ulcer in a 35-year-old Caucasian man.